ORGANIZATIONAL ISSUES OF INTERNAL AUDIT SERVICE IN INSURANCE ORGANIZATIONS - Abduraimova Maftunakhan Akhmatovna (Research Parks Publishers, 2023)
The article describes organizational issues in the organization of internal audit service in insurance organizations. In this, an opinion was given about the goals, tasks and importance of introducing internal audit in insurance organizations. Also, the principles of organizing the audit of documents collected by the auditor in the organization of the internal audit service in insurance organizations are also emphasized. In the organization of the internal audit service in insurance organizations, emphasis is also placed on audit activities